2008
DOI: 10.1186/1471-2415-8-6
|View full text |Cite
|
Sign up to set email alerts
|

A five-year retrospective study of the epidemiological characteristics and visual outcomes of patients hospitalized for ocular trauma in a Mediterranean area

Abstract: Background: To determine the epidemiological characteristics and visual outcome of ocular trauma in southern Italy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
138
9
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(199 citation statements)
references
References 41 publications
43
138
9
9
Order By: Relevance
“…Other studies on trauma epidemiology confirm a male predominance, with a male : female ratio varying between 1.25 and 5.5. 3,14,18,19 The male : female ratio in this study was 1.42. This may reflect the more aggressive characteristics of male behaviour even in childhood aged.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other studies on trauma epidemiology confirm a male predominance, with a male : female ratio varying between 1.25 and 5.5. 3,14,18,19 The male : female ratio in this study was 1.42. This may reflect the more aggressive characteristics of male behaviour even in childhood aged.…”
Section: Discussionmentioning
confidence: 95%
“…A higher OTS score is typically associated with a better prognosis. 4,9,19,26 In this study we used the POTS in pediatric penetrating eye injuries (Table 2); it is similar to the OTS, but not the same. We classified injuries using that score and assessed relationship of the final VA and the POTS.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the United States Eye Injury Registry (USIER) showed that 13% of the eye injuries were due to recreation or sports; and they were characteristic of young people under 30 and males [3]. Similarly, Cillino et al [4] found that sport activities were one of the causes of eye injury in men (17.5%), while in women the prevalence was more homerelated or outdoor activities. Most of these injuries are considered preventable [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Sports goggles with polycarbonate lenses are suitable for sports such as basketball, football, tennis, baseball or softball [4,5]. However, in other sports like, field or ice hockey, and paintball the most appropriate option is to use full face protection [3].…”
Section: Common Injuries In Sport Practicementioning
confidence: 99%
See 1 more Smart Citation